Analisis Faktor Yang Mempengaruhi Luas Pengungkapan Dalam laporan Keuangan Tahunan - Eko Hariyanto (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2010)
This research is conducted as mean to know the influence of the firm characteristics that it is predicted influence the extent of disclosure. Company characteristics as independent variables in this research are firm size, and company status , while the dependent variable is the extent of disclosure obtained from total score of disclosure on company annual report. The list of disclosure items based on BAPEPAM rules No. VIII. G2/ Kep-38-PM-1996, Financial Accounting Standard (SAK) and SE BAPEPAM No. 02/PM/2002. Based on descriptive analysis, this research found a systematic differentiation of the extent disclosure on company annual report. The result of classic assumption test shows that regression model had fulfilled the requirement which are normality, heteroskedasticity, multicolinearity and autocorellation. Using multiple linear regressions analysis, this research has shown that firm size, kind of industry and company status for together have significant impact to the extent of disclosure and the firm size and the kind of industry have significant impact partially.The implication is the company which is smaller had better try to involve the information of annual report. Every industry has different risk among each other, this situation can influence the extent of disclosure from the company that listed in Indonesian Stock Exchange. This research is the efforts related with the arrangement of annual report must be continuously improved, especially which has related with information disclosure such as company age, company profile and public stock portion can be used.